Case Study Protocol to Evaluate the Impact of Training Intervention on Cleaners' Knowledge Level, Perceptions and Practices regarding Correct Cleaning Techniques at Selected Care Facilities in Limpopo Province, South Africa - Takalani Grace Tshitangano (MDPI AG, 2024)
Despite being preventable, healthcare-associated infections are known primary causes of patient mortality and morbidity, threatening global public health. Though it is believed that one competent and dedicated cleaning staff member given the right tools and enough time can prevent more health-care-associated infectious diseases than a room full of doctors and nurses can cure, it was discovered in Letaba Hospital of the Limpopo Province, South Africa, that knowledge and practices of infection control among cleaning staff were not optimal. The proposed study aims to evaluate the impact of training interventions on cleaners' knowledge levels and practices. In Phase 1, cleaners' pre-training knowledge level, practices, and perceptions regarding correct cleaning techniques will be assessed through qualitative, individual, in-depth interviews. The initial question will read, "Describe the steps you follow when cleaning at this health facility and why?" In Phase 2a, a cleaning training program will be developed based on the South African Qualification Authority ID 118730 Healthcare Cleaner: Occupational Certificate Curriculum and the Center for Diseases Control and ICAN's Best Practices for Environmental Cleaning in Healthcare Facilities in Resource-Limited Settings. In Phase 2b, a cleaning training intervention will be implemented. In Phase 3, cleaners' post-training knowledge level, practices, and perceptions will be reassessed and compared to pre-training findings. The Standard Protocol Items: Recommendations for an Interventional Trial, commonly known as SPIRIT, guided the development of this protocol. This protocol received ethical clearance number FHS/22/PH/04/3005 in August 2023 from the University of Venda Human and Clinical Trials Research Ethics Committee. The protocol approval was granted by the Limpopo Provincial Department of Health (LP_2022-05-028) in October 2023. This protocol is registered with the South African National Clinical Trial Registry. The findings of this study may provide baseline data upon which healthcare facilities' cleaner training qualification curriculum may be developed. In addition, this protocol contributes to the application of qualitative methodology in an intervention trial.